(untitled) (International Journal of Food and Nutritional Sciences, 2022)
With the start of the Green Revolution and globalization, farming became more intensive in emerging nations.Punjab and Haryana are the pioneer states of India where increased agricultural productivity due to Green Revolution was witnessed. With passage of time and shortage of land resources due to increasing population, only an intensive strategy for food production was the viable option for states of Punjab and Haryana to maintain the agricultural productivity.Cropping intensity is an indicator which helps in determine that how often same parcel of land is being cultivated in one agricultural year. Thus, higher cropping intensity pinpoints towards the intensification of agriculture in that region. These two states have highest cropping intensity and it was 190.28 percent in Punjab and 186.93 percent in Haryana. The present study aims to evaluate the spatio-temporal variations and changes in cropping intensity.